Organic Farming Improves Soil Aggregation and Organic Carbon Status in the Rice-Wheat Cropping System in an Inceptisol - Paulson Thomas; Dinesh Kumar; Debarati Datta; Ritesh Saha; Debashis Chakraborty (Journal of the Indian Society of Soil Science, 2023)
The paper deals with the long-term (11 yr.) impact of organic farming on soil aggregates and different forms of organic carbon namely, total, oxidizable and recalcitrant pools, and particulate organic matter-C in rice-wheat (R-W) and rice-wheat-mung bean (R-W-M) rotations in an Inceptisol. Soil aggregate stability (AS) was higher in R-W-M (86%) in the 0-7.5 cm layer than under R-W (83%). Organic nutrients resulted in 88-94% aggregate stability compared to 75% in the control (no nutrient supply). The R-W rotation recorded greater aggregate mean weight diameter (MWD) of 0.50 and 0.52 mm compared to 0.43 and 0.40 mm in R-W-M in 0-7.5 and 7.5-15 cm layer, respectively. The farmyard manure (FYM) with crop residues resulted in the highest total organic carbon (CTOC) content in both layers (1.88-2.05%). Large amounts of particulate organic matter-C (CPOM) were recorded in organic nutrient treatments as 0.4-0.5% in 0-7.5 cm compared to 0.3-0.4% in 7.5-15 cm layer. The MWD of aggregates correlated the best with CPOM (r=0.51) among the C pools, while AS showed the highest correlation with CTOC (r=0.53). The tensile strength of aggregates showed wide variability among the organic treatments and decreased with an increase in CTOC. An overall consideration of the results indicates that crop residue application with vermicompost or FYM has the most potent impact on soil physical condition and soil C status, holding a promise for sustaining the R-W cropping system in Inceptisol.